LEGAL PROTECTION FOR WOMEN IN THE PERSPECTIVE OF THE LAW ON THE ELIMINATION OF SEXUAL VIOLENCE - Shinta M Hasibuan; Mompang L. Panggabean; Aartje Tehupeiory (Sean Institute, 2023)
The objectives of this research are as follows: first, to find out the construction of Legal Protection of Women contained in Law No. 12 of 2022; and second, to find out the obstacles and challenges that may exist in the application of Legal Protection of Women in Law No. 12 of 2022. Some of the theories used in this research include Aristotle's theory of justice, reviewed by Theo Huijbers, Gustav Radbruch's theory of legal certainty, and the theory of victimology. The method used in this research is the normative juridical method, considering that the starting point of the research is the analysis of laws and regulations. The approach used in this research is to use a legislative approach where the material gathered is done by using library research. This study’s results are comprehensive legal protection, the recognition of various acts of sexual violence, the establishment of protection institutions such as P2TP2A, the increase in legal sanctions, and the empowerment of victims.